IDENTIFIKASI MISKONSEPSI DAN KONFLIK KOGNITIF FISIKA: KASUS TERKAIT PERUBAHAN KONSEPTUAL - Hidayatullah, Zul; Jumadi, Jumadi; Nadhiroh, Nuraini; Kartika, Endah; Nuha, Azizah Ainun; Erlangga, Sony Yunior (EDUSAINS, 2020)
IDENTIFICATION OF MISCONCEPTION AND COGNITIVE CONFLICT OF PHYSICS: A CASE RELATED TO CONCEPTUAL CHANGEAbstractMisconceptions still often occur when learning physics. This study aims to identify students' misconceptions and their relationship with cognitive conflict in terms of conceptual change. This research used mixed methods explanatory design methods. The subjects in this study were three students from SahabatQu High School, Yogyakarta. The students studied were categorized into three, namely low, medium, and high ability students. Information related to student abilities is obtained from physics teachers and student learning test results. A conceptual change interview guide, conceptual change observation sheet, cognitive conflict questionnaire, and parabolic motion material misconceptions tests were used as supporting instruments to obtain the desired results in research. The learning process uses a PhET simulation. The results showed that high, medium and low ability students still had misconceptions when learning parabolic motion material. Cognitive conflict in high, medium and low ability students is included in the low and moderate categories with a percentage of 8.33% - 41.67%. All students have not been able to experience the four thought processes so that there are still misconceptions on some topics such as the highest point and the farthest distance based on the projectile motion's elevation angle. AbstrakMiskonsepsi masih sering terjadi pada saat pembelajaran fisika. Tujuan penelitian ini adalah mengidentifikasi miskonsepsi siswa dan hubungannya dengan konflik kognitif ditinjau dari perubahan konseptual. Penelitian ini menggunakan metode mixed methods explanatory design. Subjek pada penelitian ini adalah 3 siswa yang berasal dari SMA Sahabatqu, Yogyakarta. Siswa yang diteliti dikategorikan menjadi 3 yaitu siswa berkemampuan rendah, sedang, dan tinggi. Informasi terkait kemampuan siswa diperoleh dari guru fisika dan hasil tes belajar siswa. Pedoman wawancara perubahan konseptual, lembar observasi perubahan konseptual, angket konflik kognitif, dan tes miskonsepsi materi gerak parabola dijadikan instrumen pendukung untuk mendapatkan hasil yang diinginkan dalam penelitian. Proses pembelajaran menggunakan simulasi PhET. Hasil penelitian menunjukkan bahwa siswa berkemampuan tinggi, sedang, dan rendah masih memiliki miskonsepsi pada saat pembelajaran materi gerak parabola. Konflik kognitif pada siswa berkemampuan sedang dan rendah termasuk dalam kategori rendah dan siswa berkemampuan tinggi termasuk dalam kategori sedang. Seluruh siswa belum mampu mengalami empat proses berpikir sehingga masih menyisakan miskonsepsi pada beberapa submateri seperti titik tertinggi dan jarak terjauh berdasarkan sudut elevasi gerak parabola.